The Semiotic Features in the Augustian's text - Shbani , Monzer; Ismael , Afraa; Hmaidoush, Lina (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research handles the Semiotic Features in the Augustian's text an attempt to discover its nature and implication. It tackies the Semiotic theme, its concepts and relation to the Sociological Cultural realities of modern semitians. then it discusses the concept of sign and its relation to interpretation in this text showing its distinct features, Symbolic language which makes us delve deep into this text trying to open broaden horiozons via searching deep into existence to decipher hidden meanings of symbos in the external existence of things. It also deals with the speciality of sign to Augustein in which the theological perspective played the major role. It also aims at specifying the differences and similarities with some modern semitics to talk eventually about kinds of sign trying to end up with some results that help us comprehend the Augustian's text.